Effect of Water Content on Free Fatty Acid Value Reduction in Nyamplung Crude Oil (Calophyllum Inophyllum L.) Extracted by N-Hexane Solvent and Using Factorial Design Experiment - Maulidinoor, Farah Salsabillah; Broto, Wisnu (Waste Technology, 2023)
This study aims to determine the effect of water content on free fatty acid levels in nyamplung (Calophyllum inophyllum L.) seed oil. Nyamplung fruit seeds have a relatively high oil content ranging from 40%-73%, which can be used as a biodiesel raw material. Nyamplung seed oil has a high FFA content that ranges from 15%-30%. The process of extracting nyamplung seed oil is done by the soxhletation method because it is considered the most efficient and uses nhexane solvent, which has non-polar properties and can increase oil yield (more than 50%). This study will use the factorial design level 2 method to determine the most influential process variables to produce optimum operating conditions in making nyamplung seed oil with the lowest FFA content. The variables used in this study are moisture content (8% and 12%), particle size (15 mesh and 25 mesh), and the ratio of materials and solvents (1:1 and 1:3). The analysis results showed that water content had the most significant influence on free fatty acid content with a value of 0.25 and the lowest free fat content of 13.30%.